A comparative study on the quality of life and resilience of mothers with disabled and neurotypically developing children in Iran. Issue 6 (June 2021) - Fereidouni, Zhila; Kamyab, Amir Hossein; Dehghan, Azizallah; Khiyali, Zahra; Ziapour, Arash; Mehedi, Nafiul; Toghroli, Razie
Abstract: Background: Mothers who take care of their disabled children usually suffer from several problems, such as physical, psychological, and social problems. The disability of children can also directly impress the quality of their mothers' lives. This study is going to check out how the disability of children affects the quality of life of the mothers. Objective: This study was conducted to compare the quality of life and resilience of mothers with disabled and typically developed children in Fasa, Iran. Methods: The subjects of this cross-sectional study were 240 mothers (120 mothers having disabled children and 120 mothers with typically developed children) referring to Fasa State Health Centers and Fasa State Welfare Office. They were randomly selected and included in the study. All samples were collected by the convenience sampling method. The data were collected by using the World Health Organization Quality-of-Life Scale (WHOQOL-BREF) and the Connor-Davidson Resilience Scale (CD-RISC). The collected data were then analyzed by the SPSS (v.22) software. The results of the descriptive statistics, Chi-square, independent t-test, and Pearson correlation coefficient were at a significant value of P < 0.05. Results: The mean score of quality of life of mothers with disabled children on physical, psychological, social, and environmental domains was lower than that of mothers with neurotypically and statistically significant (p < 0.05); however, the mean scores on the resilience of mothers in both groups were not significantly different (p = 0.43). The results of the linear regression analysis showed that, having a disabled child (P < 0.001, t = 10.141), level of education (P < 0.001, t = 2.031), and resilience (P < 0.001, t = 8.205) affect the quality of life. The lower the education level is, the lower the quality of life. And higher resilience increases the quality of life. Conclusion: The quality of life of mothers with disabled children was lower compared to mothers with typically developed children, but there was no difference between mothers' resiliency in these two groups. These results suggest the necessity to provide supportive and therapeutic programs for improving the quality of life of mothers with disabled children. Abstract : Quality of life; Resilience; Mothers with disabled children; Iran